2022
DOI: 10.1007/s00268-022-06621-x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Care Pathways in Low‐ and Lower‐Middle‐Income Countries: Systematic Review and Narrative Synthesis

Abstract: Background Safe and effective care for surgical patients requires high-quality perioperative care. In high-income countries (HICs), care pathways have been shown to be effective in standardizing clinical practice to optimize patient outcomes. Little is known about their use in low- and middle-income countries (LMICs) where perioperative mortality is substantially higher. Methods Systematic review and narrative synthesis to identify and describe studies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Despite the importance of research in the area of perioperative care, there remains a paucity of evidence on fast-track surgery pathways in the developing world. A recent systematic review by Patel et al [25] identified twenty-seven eligible articles on perioperative care pathways conducted in Low-and Middle-Income Countries (LMIC) published since the year 2000, and only one of them (in obstetrics and gynaecology) [26] was performed in Sub-Saharan Africa. The search of the literature additionally revealed two citations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of research in the area of perioperative care, there remains a paucity of evidence on fast-track surgery pathways in the developing world. A recent systematic review by Patel et al [25] identified twenty-seven eligible articles on perioperative care pathways conducted in Low-and Middle-Income Countries (LMIC) published since the year 2000, and only one of them (in obstetrics and gynaecology) [26] was performed in Sub-Saharan Africa. The search of the literature additionally revealed two citations.…”
Section: Discussionmentioning
confidence: 99%
“…Adopting ERAS protocols marks a significant shift toward more efficient, patient-focused care, a viewpoint echoed by Patel et al [ 17 ]. Their advocacy for multimodal perioperative care strategies aligns closely with our findings, underscoring the potential of these protocols to enhance the overall surgical experience for patients.…”
Section: Reviewmentioning
confidence: 99%